Kulturmöte i gränslandet mellan motsättningar och möjligheter : Strategier för att tillvarata kulturmötens kreativa potential - Cvetković, Anita (Mittuniversitetet, Institutionen för samhällsvetenskap, 2008)
Encounters and relations between people with different cultural backgrounds tend to be primarily discussed in terms of exclusio, prejudice and conflict. This thesis focuses on the creative aspects of intercultural encounters. The starting point is that the parties involved sometimes succeed in avoiding the latent conflicts between cultures by acting trategically. The aim of this thesis is to increase understanding of the possibilities represented by intercultural encounters and to identiy the strategies employed by the actors who try to deal with the contrasts and dilemmas involved in encounters with other peopl with different cultural experiences, identities and methods. The empirical part of the thesis is based on four qualitative case studies that are characterised by rather positive co‐operation between the actors in the intercultural encounter, i.e. "immigrants" and the majority society in Sweden. The empirical data are based on 45 individual interviews, two focus group discussions and a number of minor observations made in the inland part of northern Sweden, where the case studies were carried out. The principal result of this research is that the actors begin to see culture as a possibility when they find themselves in a osition where they feel obliged to change their established patterns of behaviour, due to some sort of crisis situation. The strategies used by the actors to deal with culture conflicts can be divided into intra‐group strategies and inter‐group strategies. The former attempt to achieve relative homogeneity between the competing groups in the field of the intercultural encounter, while the latter illustrate how the participants deal with what they experience as differences. Four inter‐group strategies have been identified: 1) the status quo strategy, 2) the loose coupling strategy, 3) the selective strategy and 4) a culture mixing strategy. The latter three are characterised by innovative combinations that organise the existing cultural elements in a meaningful way These strategies result ...